Polymorphic nature of 332 〈 113 〉 twinning mode in BCC alloys. Issue 5 (4th May 2022) - Kwasniak, P.; Sun, F.; Mantri, S.; Banerjee, R.; Prima, F.
Abstract : Unprecedented mechanical properties of the novel TWIP/TRIP titanium alloys are controlled by 332 < 113 > twinning and stress-induced martensitic transformation, which can operate separately, simultaneously or even in synergy, following a still unclear atomic-scale mechanism. Using ab initio calculations and experimental observations, we show that 332 < 113 > twinning can be described as a polymorphic solid-state transformation able to produce either twinned or martensitic structures with a unified transformation path. The required lattice strains and atomic shuffles are provided by the shear-shuffle mechanism of twin operation, of which trajectory, due to accompanied atomic relaxation, is not linear and strongly influenced by β phase stability. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Plasticity of metastable alloys is extended by the concept of polymorphic deformation modes of which path is sensitive to the composition of the alloy, enabling stabilization of the intermediate transition states.